A preliminary study, using electron and light-microscopic methods, of axon numbers in the fornix in autopsies of patients with temporal lobe epilepsy - ERCAN, FERİHA; ÖZDOĞMUŞ, NECMETTİN ÖMER (SPRINGER, 2009)
Our objective was to show morphological changes of the fornix in autopsies of patients with temporal lobe epilepsy, which may potentially serve for post-mortem diagnosis. Epileptic and non-epileptic autopsy brains were obtained from the council of forensic medicine between the years 2005 and 2007. In both non-epileptic and epileptic autopsies the mean cross-sectional areas and fiber densities of the right and left fornices were calculated and analyzed. The numbers of myelinated and unmyelinated fibers, and the total number of fibers forming each fornix were counted. The total number of fibers in the right fornix was always greater than in the left fornix, in both epileptic and non-epileptic autopsies. The mean total number of fornix fibers was significantly reduced in epileptics compared with non-epileptics, in both the right (p = 0.043) and left (p = 0.043) sides. The electron-microscopic sections showed that myelinated axons outnumbered unmyelinated axons in both epileptic and non-epileptic autopsies. However, the reduction in the number of unmyelinated fibers was only statistically significant for the right fornix in right epileptic autopsies (p = 0.021). Although the reduction in the number of myelinated fibers was not statistically significant, electron-microscopic evaluations showed myelin degeneration of the myelinated fibers in the right fornix of the right temporal lobe in epileptic autopsies. In conclusion, our results suggest that unmyelinated fiber loss is functionally important, and may have functional consequences of diagnostic value.
Keywords: Axon; Epilepsy; Fornix (brain); Hippocampus; Nerve fibers; Myelinated; WHITE-MATTER TRACTS; HIPPOCAMPAL SCLEROSIS; MAMILLARY BODY; MR; SEIZURES; ABNORMALITIES; HYPOTHALAMUS; ASYMMETRY